The Effectiveness of the Rehabilitation of Islamic Boarding Schools Responsibilities as a Method of Healing of Drug Abuser - Jawade Hafidz (Jurnal Daulat Hukum, 2022)
This research aims to know about rehabilitation, narcotics addicts and narcotics abusers who are proven victims are required to undergo and carry out medical rehabilitation or undergo social rehabilitation. In terms of social rehabilitation, Article 57 of Act No. 35 of 2009 states that "other than through medical treatment and/or rehabilitation, the healing of narcotics addicts can be carried out by government agencies or the community through religious and traditional approaches". The approach used in this research is normative juridical or library law research or doctrinal legal research. Generating Religious Awareness is a process rather than the accumulation of all life experiences which are recognized as reflections of philosophy and outlook on life, thus presenting positive values. Nashori mentions that the state of consciousness is a process of maturation resulting from the development of religious character and continued as a spiritual journey. The awareness process used is termed in the Tarekat Qodiriyah Naqsyabandiyah (TQN) as Tazkiyatun Nafsi or cleansing the soul from various diseases or impurities of the heart, such as: stingy, ambitious, jealous, stupid, hedonistic, and various other despicable morals. Pondok Pesantren not only intends to awaken victims of narcotics abuse, but by using the method of Islamic teachings or religious therapy for the healing process or rehabilitation for patients or victims of narcotics abusers. There are several obstacles faced in rehabilitation activities in Islamic boarding schools for narcotics abusers, including